Fitness Technology in Education: A Bibliometric Analysis of Current Trends and Future Directions - Noerpratomo, Ramdhani Hanwar; Fitri, Mustika; Apriady, Hilmy; Ockta, Yovhandra (STKIP Singkawang, 2024)
This study conducts a bibliometric analysis to investigate trends in fitness technology research, aided by the VOSviewer software. Using relevant keywords, a comprehensive search was performed in the Scopus database, resulting in the extraction of 482 documents pertaining to fitness technology trends. The analysis revealed a significant growth trajectory in fitness technology publications, with development starting in 2013 and experiencing a notable increase in the 2020s. Productivity and impact were assessed across countries, with the United States, China, Italy, and the United Kingdom emerging as the most prolific contributors. Notably, China led in productivity with 132 publications, while the United States held the highest impact with 5196 citations. Furthermore, author keyword analysis identified three distinct clusters, highlighting interrelated themes such as